Perubahan tahap pencahayaan dalam bilik darjah di sebuah sekolah pendidikan khas cacat penglihatan dan perbandingan tahap pencahayaan di bawah keadaan pencahayaan yang berbeza - Wan Nur 'Amirah Ibrahim,; Zainora Mohammed,; Norliza Mohamad Fadzil,; Sumithira Narayanasamy,; Mohd 'Izzuddin Hairol, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Illumination is one of the important physical aspects that influences comfortability during learning session particularly among visually impaired students. The purpose of this study was to determine changes in illumination level in classrooms during learning session at Sekolah Menengah Pendidikan Khas (SMPK), Setapak. The second objective was to compare the illumination level in the classrooms under three different lighting conditions: daylight only, with additional artificial light and with removal of obstructions to daylight. Illumination levels in 17 classrooms was measured at one hour interval, between 8 am to 1 pm for the first stage and 19 classrooms under three different lighting conditions from 11 am to 12 noon for the second stage, using ILM1335 (ISO-TECH, Taiwan) digital luxmeter. Illumination level increased significantly from 8 am to 11 am (One-Way Repeated Measures ANOVA: F(2.14, 34.26)=76.49, p<0 .001) and was maximum at 1 pm. The illumination level was highest for the condition of daylight with additional artificial light (One-Way Repeated Measures ANOVA: F(2,34)=110.51, p<0.001) compared to other conditions. Illumination levels for daylight without obstruction was significantly higher than daylight only (pairwise comparison: p=0.001). Classroom illumination level was lowest in the early morning. However, classroom illumination can be increased either by removing the obstructions to daylight or with additional artificial lighting.